FACTORS ASSOCIATED WITH WORK-RELATED BURDEN AMONG CAREGIVERS OF OLDER ADULTS IN MONTES CLAROS, BRAZIL (REMUNOM, 2025)
Objective: To identify factors associated with work overload among elderly caregivers. Method: Quantitative, cross-sectional, and analytical study with a sample of 107 caregivers, both formal and informal. Data collection used a sociodemographic questionnaire and the Zarit Burden Interview to measure caregiver burden. Data were analyzed using binary logistic regression with SPSS 22.0 software. Results: It was observed that 90.7% of participants presented some level of burden, with 29% classified as having severe burden. Daily care time, especially over ten hours, was identified as the main factor associated with severe burden, with a significant increase in the odds of its occurrence. Final Considerations: Caregiver burden among elderly caregivers represents a relevant public health problem, with implications for the quality of care provided and caregivers’ physical and emotional health. The findings highlight the need for public policies and targeted interventions to reduce caregiving hours, promote self-care, and strengthen support networks.